DAILY FOLLOW UP NOTES’ ACCURACY ACCORDING TO SOAP (SUBJECTIVE, OBJECTIVE, ASSESSMENT, PLAN) FORMAT - shaista Arshad; Bushra Shirazi; Zubia Masood; laeeqa Ahmed (Khyber Medical University Journal, 2015)
A